ASYMMETRIC INFORMATION DAN DIVIDEND DECISION PADA PERUSAHAAN ASURANSI DI INDONESIA - Sumani, Sumani; Puspitasari, Novi; Sari, Cindi Fatika (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The objective of this study is to analyze the effect of asymmetric information on dividend policy. Asymmetric information in this study was proxied by four variables, i.e., the bid-ask spread, earnings forecast error, firm size, and growth opportunities. Dividend policy was proxied by the dividend payout ratio. The population of this study was insurance companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sample was selected using a purposive sampling technique. The analysis method used was multiple linear regression. The results showed that the variable of earnings forecast error had a significant positive effect on dividend policy. However, the variables of the bid-ask spread, company size, and growth opportunities did not affect dividend policy. The result of the coefficient of determination test showed that the independent variable could influence the dependent variable by 41.2%. Keywords : asymmetric information, dividend policy, insurance companies